What Could Be, But Never Has Been: Horizons of Human Rights and Racial Justice (Medicine Anthropology Theory, 2021)
The US’s authority as chief enforcer of human rights grows increasingly illusory as civil unrest brings the quotidian nature of racialised human rights violations in the US into a frame shared by authoritarian regimes. This reality animates my analysis of how an organisation I call Doctors for Humanity (DfH) finds its footing in a terrain of human rights enforcement that is shifting from a global to a domestic focus. The US is not an actual space of freedom but often represents the limit of possible freedoms. This horizon evokes something that always could be but never has been and unmasks what I analyse as a constitutive unfreedom at the heart of liberalism in American empire. To attend to human rights violations in the US is to undermine American authority and its right and responsibility to make claims about the actions of other nations. As a future physician and human rights advocate invested in racial justice, I illuminate the paradoxes of ethical action within a context where the possibility of freedom for some depends upon the unfreedom of others. To effectively police human rights from this perspective necessitates the deconstruction of the US as a space of freedom, pointing instead towards a praxis of global human rights which lives up to the concept’s aspirational universality.